Influence of Intensive Care Unit Enlightenment on Premature Infants on Functional Brain Maturation Assessed by Amplitude-Integrated Electroencephalograph - Tandircioglu, Umit Ayse; Guzoglu, Nilufer; Gucuyener, Kivilcim; Aliefendioglu, Didem (American Journal of Perinatology, 2019)
Objective Amplitude-integrated electroencephalograph (aEEG) presents a valuable tool for functional brain maturation of preterm infants. However, the effect of enlightenment on functional brain maturation of premature infants has not been investigated. We aimed to do this with aEEG.Study Design A total of 32 infants, 30 to 35 gestational weeks, were involved in the study. They were randomly distributed into three groups in which different lighting protocols were applied. In group 1, the infants' incubators were covered for 24 hours. In group 2, the infants' incubators were open for 24 hours. In group 3, the infants' incubators were covered for 12 hours and open for another 12 hours. The infants are evaluated with aEEG recordings done on the 3rd (first measurement) and 10th days (second measurement) along with the Burdjalov scoring. Analysis of aEEG recordings was performed, based on sleep–wake cycles (SWCs), upper and lower margin amplitudes, narrowband and broadband of SWC, and bandwidth of SWC.Results At first, the narrowband lower amplitudes in group 1 were higher than those of the other groups (p = 0.042), but the difference was not significant in the second measurement (p = 0.110). The Burdjalov scores were higher in group 1 and group 3 on 10th day, though not statistically significant (p = 0.871). When the infants were re-evaluated according to the gestational weeks, the Burdjalov scores of the two groups less than 34 weeks (30–31 and 32–33 weeks) were similar, whereas 34 to 35 weeks were higher when compared with those of the two groups.Conclusion The difference observed between groups in terms of narrowband lower amplitude in the first measurement may reflect the effect of intrauterine environment rather than enlightenment at the same gestational age because it was made on the third day. However, the fact that all groups have similar results on day 10 suggests that other factors in the intensive care setting may diminish the effect of enlightenment. Burdjalov scores are associated with maturation, and high scores found in the 34- to 35-week group suggest that the 34-week maturation might be a threshold for SWC and development in our group sample.
Keywords: premature; functional brain maturation; aEEG